Pembaharuan Sistem Hukum Undang-Undang Nomor 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana - Barasa, Abdur Rachman Parlindungan; Saputra, Wahyudi (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2025)
Criminal law tends to appear rigid and prioritizes formality, which ultimately creates the perception that criminal law is formulated to impose retribution. For instance, imprisonment, which is always used as a tool of retribution as stipulated in Article 10 of the Criminal Code (KUHP). Based on this perspective, law enforcement officers tend to always qualify an act as a criminal offense once it fulfills the provisions of the Criminal Code, and it consistently ends in the criminal justice process, which then results in a prison sentence. The purpose of this research is to examine the transformation of the enactment of Law Number 1 of 2023 concerning the Indonesian Criminal Code as a significant turning point in the history of Indonesian criminal law. The normative juridical writing method is a legal literature study conducted by examining the norms of positive law as stipulated in legislation such as Law Number 1 of 1946 on Criminal Law Regulations, Law Number 73 of 1958, and Law Number 1 of 2023 concerning the Indonesian Criminal Code. The data in this research was collected through literature studies, with secondary legal materials in the form of books, journals, and other literature. The analysis in this research employs a conceptual and historical approach. The urgency of change arises because the old Criminal Code (WvS) is considered incomplete or unable to accommodate various issues and the evolving dimensions of new types of criminal offenses, which of course are in line with the development of thought and the aspirations of societal needs. The Criminal Code represents the embodiment of the idea of monodualistic balance, which, when implemented in Indonesia’s national criminal law, will provide valuable insights into effectiveness in legal practice.